2005
DOI: 10.1021/la050656b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tetraoctylammonium-Protected Gold Nanoparticles with Improved Stability

Abstract: This paper shows that an introduction of thiosulfate anions in place of bromide anions greatly improves both chemical and thermal stability of tetraoctylammonium-protected gold nanoparticles. Tetraoctylammonium thiosulfate [(Oct)4N+-O3SS]-protected gold nanoparticles are synthesized by the reduction of (Oct)4N+-AuCl4 to Au(I)-SSO3-, followed by the addition of sodium borohydride. The presence of thiosulfate anions instead of bromide anions on the surface of gold nanoparticles results in a significant dampening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 14 publications
(35 reference statements)
6
78
0
Order By: Relevance
“…Although the kinetics of immobilization of TOAB-AuNPs were not studied in the past, it has been reported that binding of TOAB ions with AuNPs is labile and can be easily exchanged by other molecules [35,36].…”
Section: Electrochemical Characterization Of Immobilized Aunpsmentioning
confidence: 99%
“…Although the kinetics of immobilization of TOAB-AuNPs were not studied in the past, it has been reported that binding of TOAB ions with AuNPs is labile and can be easily exchanged by other molecules [35,36].…”
Section: Electrochemical Characterization Of Immobilized Aunpsmentioning
confidence: 99%
“…1) [11]. Herein, we report through investigations of the stability of both Oct 4 N +− O 3 SS-IMPCs and Oct 4 N +− BrIMPCs upon chemical treatments and solid-phase heating treatments.…”
Section: Introductionmentioning
confidence: 99%
“…However, the unsatisfactory long-term stability of ionic surfactant-protected gold nanoparticles has limited the broader use of these nanomaterials. The removal of solvents from solution containing ionic monolayer protected nanoparticles caused a complete agglomeration of particles and resulted in the formation of insoluble materials [8,10,11]. In addition, these particles decomposed by heating treatments at moderately low temperature [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Recently, a great deal of methods have been developed to prepare stable gold nanoparticles with controllable size. The synthesized gold nanoparticles are always capped with a certain stabilizer, which involves alkanethiols, [2] amines, [3] nucleotides, [4] and polymers, [5] to avoid the aggregation of gold nanoparticles resulting from Van der Waals attractions. [6] One recent research activity regarding the application of gold nanoparticles focuses on their catalytic activity for many reactions, such as glucose oxidation, [7] alcohol oxidation, [8] CO oxidation, and propylene expoxidation.…”
Section: Introductionmentioning
confidence: 99%